A non-spatial account of place and grid cells based on clustering models of concept learning - Robert M. Mok (Nature Portfolio, 2019)
Spatial maps in the medial temporal lobe (MTL) have been proposed to map abstract conceptual knowledge. Rather than grounding abstract knowledge in a spatial map, the authors propose a general-purpose clustering algorithm that explains how both spatial (including place and grid cells) and higher-dimensional conceptual representations arise during learning.